Mobile Learning Platform for E-Learning - Chis, George; Grebla, H.; Stanca, L. (International Journal of Interactive Mobile Technologies (iJIM), 2009)
The fast changing or the development of technologies induces the need to process the information in key moments in different locations. Thus, not only those who are learning need mobile tools of learning, but also those who are trainers need mobile tools for preparing the classes, for coordinating the educational activities. On this background, new patterns had been developed based on its main principles, starting with the evolution of technology. Based on these modifications we are going to present a mobileâ??learning system which we intend to integrate with our E-learning system..